Thermal Comfort and Sustainability in University Classrooms: A Study in Mediterranean Climate Zones - Pilar Romero; María Teresa Miranda; Rui Isidoro; José Ignacio Arranz; Víctor Valero-Amaro (Applied Sciences)
Thermal comfort in educational environments affects not only students’ well-being but also their concentration and academic performance. In the context of climate change, university classrooms in Mediterranean climates face particular challenges due to higher and more variable temperatures. This study evaluates thermal comfort in classrooms in southern Portugal, comparing natural ventilation (NV) and air-conditioning (AC) modes. Through environmental measurements and student surveys, thermal perceptions, preferences and factors such as position within the classroom were analysed. The results reveal that NV classrooms offer sustainable benefits, but their effectiveness decreases when outside temperatures exceed 28 °C, increasing thermal discomfort. In contrast, AC classrooms maintain more stable and comfortable conditions, although they have thermal gradients that affect specific zones, such as areas near windows or air vents. This study highlights the need for hybrid strategies that prioritise NV in moderate temperatures and use AC as a support in extreme conditions. Furthermore, it underlines the importance of appropriate architectural design and specific adaptive models for Mediterranean climates, balancing thermal comfort and energy efficiency.